Non-ionic surfactant on particles removal in post-CMP cleaning. (1st February 2015) - Sun, Mingbin; Gao, Baohong; Wang, Chenwei; Miao, Yingxin; Duan, Bo; Tan, Baimei
Abstract The effect of a non-ionic surfactant on particles removal in post-CMP cleaning was investigated. By changing the concentration of the non-ionic surfactant, a series of experiments were performed on the 12 inch Cu pattern wafers in order to determine the best cleaning results. Then the effect of the surfactant on the reduction of defects and the removal of particles was discussed in this paper. What is more, the negative effect of a non-ionic surfactant was also discussed. Based on the experiment results, it is concluded that the non-ionic surfactant could cause good and ill effects at different concentrations in the post-CMP cleaning process. This understanding will serve as a guide to how much surfactant should be added in order to achieve excellent cleaning performance.